2015
DOI: 10.1016/j.amjcard.2015.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Left and Right Ventricular Functional Dynamics Determined by Echocardiograms Before and After Lung Transplantation

Abstract: Impaired cardiac function is considered a contraindication for lung transplantation (LT). Since right ventricular (RV) function is expected to improve after LT, poor left ventricular (LV) function is often the determinant for LT eligibility. However, the changes in cardiac function before and after LT have not yet been elucidated. Therefore, we reviewed echocardiograms obtained from 67 recipients before and after LT. In a subset of 49 patients, both RV and LV longitudinal strains based on 2D speckle tracking e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Furthermore, a retrospective study reported that pre-transplant diabetes mellitus could increase the risk of cancer after LTx, and cancer is a major source of morbidity and mortality in patients with solid organ transplantations [ 23 ]. To our knowledge, diabetes also increases the morbidity of cardiovascular diseases, which are thought to increase the mortality of patients receiving LTx [ [24] , [25] , [26] ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a retrospective study reported that pre-transplant diabetes mellitus could increase the risk of cancer after LTx, and cancer is a major source of morbidity and mortality in patients with solid organ transplantations [ 23 ]. To our knowledge, diabetes also increases the morbidity of cardiovascular diseases, which are thought to increase the mortality of patients receiving LTx [ [24] , [25] , [26] ].…”
Section: Discussionmentioning
confidence: 99%